Analisis Strategi Fungsional Sumber Daya Manusia dan Pemasaran - Gunawan Aji; Saifullah, Eef; Nikita Norma Balistik; Amelia Nabila; Intan Nurul Hidayatul Afiyah (Jurnal Riset dan Inovasi Manajemen, 2023)
The purpose of this research is to define marketing, human resources, and functional strategies. Marketing managers will be guided by this marketing functional level plan as they decide who will sell what, to whom, where, how much, and how. On the other hand, the role and purpose of marketing is to help a business achieve its goals by placing goods and services profitably in the market. This research approach is qualitative, namely research that is natural and produces descriptive information. In this study, information was collected through a research literature study from journals, books, theses, or theses that provide theoretical discussion. The findings of this study indicate that functional strategy and human resource strategy have no effect on business performance, but financial strategy and marketing strategy do.